2011
DOI: 10.1016/j.archoralbio.2011.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HMGB1 and HMGN2 in gingival tissues, GCF and PICF of periodontitis patients and peri-implantitis

Abstract: High mobility group chromosomal protein B1 (HMGB1) and N2 (HMGN2), two members of High mobility group (HMG) family, play important role in inflammation. The purposes of this study were to investigate the expression of HMGB1 and HMGN2 in periodontistis.The expression of HMGB1 and HMGN2 mRNA in gingival tissues and gingival crevicular fluid (GCF) in chronic periodontitis (CP), generalized aggressive periodontitis (G-AgP) patients and healthy subjects was detected by real-time PCR. The protein level of HMGB1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
6
35
0
Order By: Relevance
“…In the ligature model, HMGB1 expression could be compared to the expression profile of TNF- α and IL-6 from our previous study in which higher expression of these genes occurred at days 7 and 15 followed by a reduction at 30 days [29]. These in vivo results corroborate also with a clinical study that have demonstrated high levels of HMGB1 in gingival tissues and gingival crevicular fluid of chronic periodontitis patients compared to control [30]. In addition, this clinical study showed that HMGB1 responds in a similar way to other cytokines during disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…In the ligature model, HMGB1 expression could be compared to the expression profile of TNF- α and IL-6 from our previous study in which higher expression of these genes occurred at days 7 and 15 followed by a reduction at 30 days [29]. These in vivo results corroborate also with a clinical study that have demonstrated high levels of HMGB1 in gingival tissues and gingival crevicular fluid of chronic periodontitis patients compared to control [30]. In addition, this clinical study showed that HMGB1 responds in a similar way to other cytokines during disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, P. gingivalis is associated with oral squamous cell carcinomas and other chronic diseases [3, 52]. Our findings also support studies showing that HMGB1 is another possible candidate for an early inflammatory disease marker [53, 54]. Collectively, these results suggest that P. gingivalis NDK dampens the host-immune response by decreasing release of pro-inflammatory cytokine, IL-1β, and the pro-inflammatory danger signal, HMGB1, from infected GECs.…”
Section: Discussionsupporting
confidence: 87%
“…Thirteen studies showed higher levels of IL-1β in PICF than healthy implant sites [7,21,22,30,35,36,41-47]. Of the 10 studies assessed TNF-α, 3 of them showed no relationship with this cytokine with peri-implant inflammation [7,25,43], while other 7 studies showed significant relationship with this cytokine [23,24,36,41,46-48]. These findings suggest that pro-inflammatory cytokines such as IL-1β and TNF-α are up to date, the most promising proteins to be used as markers in PICF for differentiation between peri-implantitis and healthy implants.…”
Section: Discussionmentioning
confidence: 99%